AGE RELATED CHANGES IN THE CERVICAL BACKBONE - W. Wassilev; D. Andreev (Trakia Journal of Sciences)
By using macroscopic inspection, x-ray, histological methods and contrast filling of the blood vessels, investigated were human cervical backbones of grown-up individuals 15 to 88 years old, and of fetuses, newborns and children. Besides to the vertebrae themselves, special attention was paid to the intervertebral disks and joints, as well as to the blood vessels. In the backbones of humans in the age after the fourth decade, alterations were observed in the structure of the vertebrae (mainly in the form of exostoses) and of the backbone as a whole (decrease of the cervical lordosis), in the intervertebral disks (reduction of the highness, loss of the homogeneity, destruction), and in the vertebral artery (firmness of the wall, narrowing of the lumen, and undulations).